Diagnosis of ATTR cardiac amyloidosis by 99mTc-PYP scintigraphy: case series - Santos Orihuela, Daniel Arturo (2026)
Objectives. To describe the application of the noninvasive diagnostic algorithm for transthyretin cardiac amyloidosis (ATTR) using 99mTc-PYP scintigraphy in a Peruvian hospital. Materials and Methods. A descriptive case series was conducted between 2024 and 2025 at the Nuclear Medicine Department of Hospital Nacional Guillermo Almenara Irigoyen (Lima, Peru). Six patients with clinical suspicion of ATTR referred from Cardiology were included. A standardized protocol was applied, consisting of the administration of 20 mCi of 99mTc-PYP, planar imaging, and SPECT acquisition at 1 and 3 hours. Noninvasive diagnosis was established in the presence of visual myocardial uptake grade 2–3 (Perugini scale), confirmed by SPECT and after the exclusion of monoclonal plasma cell dyscrasia. The heart-to-contralateral lung (H/CL) ratio was used as a complementary quantitative parameter. Results. The average age was 69.7±10.3 years; 66.7% were male. All patients had left ventricular hypertrophy and 83.3% had heart failure. Three patients (50%) showed grade 2–3 uptake; among them, two (33.3%) met criteria for noninvasive ATTR diagnosis (grade 3, positive SPECT, and negative monoclonal screening), with H/CL values above diagnostic cutoffs. One grade 2 case had an IgG kappa monoclonal component and was classified as inconclusive. Three patients (50%) had grade 1 uptake, considered equivocal, with H/CL values below diagnostic thresholds. SPECT was essential to confirm true myocardial uptake and avoid overinterpretation in borderline cases. Conclusions. Structured application of the noninvasive diagnostic algorithm with 99mTc-PYP is feasible in our setting and allows for appropriate classification of patients with suspected ATTR.